Biofilm in endodontics. Part II. Methods of struggle against biofilm in endodontic treatment of teeth (review of literature) (Эндодонтия Today, 2020)
The microflora in the root canal system (RCS) of teeth and dentinal tubules (DT) exists in the form of a biofilm – an organized community of microorganisms. At present, chemical and mechanical methods are used to control biofilm in RCS and DT, implying the instrumental treatment of RCS and the use of disinfectants in the form of irrigants or temporary root dressings. The purpose of this review is to analyze the accumulated information on the effectiveness of well-known modern methods and clinical strategies for combating intra-root infection to improve the quality of endodontic treatment.